2013
DOI: 10.1292/jvms.12-0351
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inactivation of the <i>p16, p15</i> and <i>p14</i> Genes Encoding Cyclin-Dependent Kinase Inhibitors in Canine T-Lymphoid Tumor Cells

Abstract: AbSTRACT. The p16, p15 and p14 genes are widely known as tumor suppressor genes in human medicine. Although a large number of genetic and epigenetic aberrations in these genes have been reported in human malignancies, canine malignancies have not been well analyzed on the aberrations of these genes. In this study, the full-length complementary DNA (cDNA) of the canine p16 gene was cloned using the 5' and 3' rapid amplification of cDNA ends methods. Based on the sequence data, primers specific for p16, p15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Primers for canine p16 have been described, based on a design within the third exon, but these do not distinguish any residual DNA in samples. 41 The results of qRT-PCR were comparable with those of microarray but across a greater dynamic range and only within the six dogs used. An exception was p53, which was downregulated substantially in stimulated samples when compared to microarray data.…”
Section: Discussionmentioning
confidence: 69%
“…Primers for canine p16 have been described, based on a design within the third exon, but these do not distinguish any residual DNA in samples. 41 The results of qRT-PCR were comparable with those of microarray but across a greater dynamic range and only within the six dogs used. An exception was p53, which was downregulated substantially in stimulated samples when compared to microarray data.…”
Section: Discussionmentioning
confidence: 69%
“…Clustering of lymphoma in related dogs has been reported, suggesting an inherited predisposition . Genetic and epigenetic changes have been identified in canine lymphoma, but the studies generally have been across multiple breeds . Studies within a breed have identified germline changes across tumor types, potentially supporting a breed‐associated cancer risk that is not specific for lymphoma …”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the tumor suppressor gene p53 are relatively rare in cL (Veldhoen et al 1998;Tomiyasu et al 2010) and although p53 expression is typically absent or of low intensity (Sueiro et al 2004;Sokolowska et al 2005), expression appears more common in older animals, high grade, and possibly T-cell lymphomas (Sueiro et al 2004). Increased Rb (retinoblastoma) phosphorylation and subsequent activation of CDK4, is common in high-grade canine T-cell lymphoma and might result from deletion of p16/loss of dog chromosome 11 (Fosmire et al 2007), hypermethylation of the CpG island of the p16 gene (Fujiwara-Igarashi et al 2014), and possibly from a deletion of the p15Àp14Àp16 locus (Fujiwara-Igarashi et al 2013). Increased Rb phosphorylation in high-grade canine B-cell lymphoma appears to correlate with c-Myc overexpression and trisomy of dog chromosome 13 (Fosmire et al 2007).…”
Section: Molecular Biology Of Canine Lymphomamentioning
confidence: 99%